2021
DOI: 10.20473/jbk.v10i2.2021.181-190
|View full text |Cite
|
Sign up to set email alerts
|

Personal Hygiene and Reproductive Health Knowledge Among Adolescents at Kampung Belajar, Surabaya

Abstract: Health knowledge is fundamental for everyone, including children. This knowledge provides understanding for children in preparation for entering puberty. However, health education which discusses personal hygiene, anemia, puberty, and healthy relationships, as well as reproductive health is still very limited in formal schools. Because of these limitations, children need to get informal education. One of the ways this is done is through health education activities at Kampung Belajar. The research objective was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…The findings of the study indicate that students' knowledge of reproductive health increased both before and after receiving education on the topic. Previous research has demonstrated that adolescents who receive education regarding sexual and reproductive health are more likely to practice personal hygiene and maintain sanitation during menstruation (Djunaedi & Sulistyorini, 2021). The function of reproductive health education in assisting adolescents in acquiring knowledge, awareness, attitudes, and healthy and responsible lifestyle behaviors is crucial.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the study indicate that students' knowledge of reproductive health increased both before and after receiving education on the topic. Previous research has demonstrated that adolescents who receive education regarding sexual and reproductive health are more likely to practice personal hygiene and maintain sanitation during menstruation (Djunaedi & Sulistyorini, 2021). The function of reproductive health education in assisting adolescents in acquiring knowledge, awareness, attitudes, and healthy and responsible lifestyle behaviors is crucial.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the evaluation of community service activities found that there was an increase in students' knowledge before and after given reproductive health education. The results of a previous study stated that adolescents who were given sexual and reproductive health education would be more likely to maintain personal hygiene and be able to practice cleanliness of the reproductive organs during menstruation [15]. The results of other studies stated that reproductive health education for adolescents is very important in helping adolescents acquire knowledge, awareness, attitudes, and healthy and responsible living behaviors.…”
Section: Fig 3 Community Service Team and The Target Communitymentioning
confidence: 99%
“…Terjadi peningkatan pengetahuan pada remaja setelah diberikan penyuluhan tentang personal hygiene dari 64,54% menjadi 79,09%. Adapun materi penyuluhan yang diberikan meliputi cara mencuci tangan, kebersihan telinga, kebersihan organ reproduksi, kebersihan kuku dan cara membersihkan organ reproduksi (Djunaedi & Sulistyorini, 2021). Perilaku kebersihan diri yang dilakukan seorang perempuan antara lain menjaga kebersihan pakaian dalam, mandi, kebersihan saat menstruasi, kebersihan setelah berhubungan intim akan berhubungan dengan tingkat kejadian infeksi alat kelamin perempuan.…”
Section: Pembahasanunclassified